2014
DOI: 10.1016/j.jom.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Justice served: Mitigating damaged trust stemming from supply chain disruptions

Abstract: a b s t r a c tThis research examines the mitigation of damaged trust stemming from supplier-induced disruptions. We used the critical incident technique on 302 buying firms in China to capture two (one successful, one unsuccessful) supplier-induced disruptions (yielding a total of 604 incidents) to test our theorizing grounded in justice theory. We find evidence that different aspects of trust damage (ability, benevolence, and integrity) can be mitigated through the supplier's selective use of appropriate jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(175 citation statements)
references
References 95 publications
5
169
1
Order By: Relevance
“…Understanding the role of organizational justice can reduce opportunistic behavior (Ireland and Webb ) and help recover trust after supply chain disruptions occur (Wang et al. ). In a critical study, Narasimhan et al.…”
Section: Literature Review: Equity Theory and Buyer–supplier Relationmentioning
confidence: 99%
“…Understanding the role of organizational justice can reduce opportunistic behavior (Ireland and Webb ) and help recover trust after supply chain disruptions occur (Wang et al. ). In a critical study, Narasimhan et al.…”
Section: Literature Review: Equity Theory and Buyer–supplier Relationmentioning
confidence: 99%
“…Related issues involving execution quality in retailing include misplaced inventory (Camdereli and Swaminathan, 2010), inventory record inaccuracy (Heese, 2007;DeHoratius et al, 2008), and backroom inventory (Gaukler et al, 2007;Eroglu et al, 2012). In addition, our research is related to studies of the impact of execution quality on the relationships between firms and their suppliers (Wang et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, since fulfillment errors make the inventory supply process less efficient by imposing unnecessary costs on retailers and suppliers alike, managers can work with suppliers toward the elimination of fulfillment errors (Wang et al, 2014). Kulp et al (2007) describe the various methods retailers use to collaborate with suppliers to reduce fulfillment errors.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies in the operations and production management literature have emphasized the importance of the perceptions of fairness for improving the performance of supply chain relationships (e.g., Griffith et al, 2006; Wang et al, 2014). For example, based on a study of 290 supply chain relationships, Griffith et al (2006) showed that the distributors’ positive procedural and distributive perceptions of fairness of supplier policies enhanced the relationship with their suppliers, decreased conflicts of interests, and increased satisfaction and performance.…”
Section: Literature Reviewmentioning
confidence: 99%